Literature Review : Analisis Senyawa Kimia sebagai Kandidat Obat Kanker Paru Menggunakan Metode Molecular Docking - Muhammad Naufal Nurhadi Hidayat; Munir Alinu Mulki; Nurlita Dwiputri Prihasti (Poltekkes Kemenkes Padang, 2025)
Lung cancer is the leading cause of death worldwide, so the development of effective drugs is urgently needed. This study aims to identify potential chemical compounds as lung cancer drug candidates through molecular docking analysis. This study used a narrative literature review method with data collected from PubMed using specific keywords such as